Fostering Social-Emotional Intelligence and Peer Collaboration in Young Learners: The Transformative Power of Prasiaga - Rusmayati, Titin; Nuraeni, Lenny; Rohaeti, Euis Eti; Nurhayati, Sri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study explores how social-emotional development in early childhood can be meaningfully enhanced through a culturally grounded, play-based extracurricular program. Specifically, it examines the impact of Prasiaga, a structured scouting-inspired model, on improving emotional regulation, autonomy, peer collaboration, empathy, and emerging leadership among children enrolled in a formal early childhood institution. Using an explanatory sequential mixed methods approach, this research was conducted at a playgroup center in Indonesia with ten participants. Quantitative data were collected through pre- and post-intervention observations across nine indicators of social-emotional competence. Qualitative data were gathered via educator interviews and visual documentation to contextualize and deepen understanding of behavioral changes. The results demonstrate a substantial increase in the emergence of targeted competencies, rising from 28.9% before the intervention to 85.6% afterward. Children showed marked gains in confidence, task independence, peer engagement, and affective expression. Educators reported improvements in classroom dynamics, including higher learner motivation and spontaneous collaborative behaviors. While leadership indicators improved modestly, subtle expressions of initiative suggest developmental momentum requiring sustained practice. The triangulation of quantitative, narrative, and visual data affirms the reliability and educational significance of these findings. This research provides empirical validation for integrating Prasiaga within national early childhood curricula. The findings position Prasiaga not as a supplementary activity but as a vital foundation for character education in early learning. By emphasizing moral formation, interactive play, and culturally resonant pedagogy, the program supports both immediate behavioral improvements and long-term developmental resilience. Future research should investigate longitudinal outcomes and program scalability to inform policy and practice in broader contexts.